From the Vocabulary of the Use of the Holy Quran for the Beautiful Names of God Almighty - Al-Subaihi, Mahmoud Suleiman Aliwi (Al-Adab Journal, 2022)
The study investigates and takes into consideration the names of God Almighty in terms of altruism in them or in the formulas that came in accordance with them or in the introduction and delay in them or in the repetition of those names or in the denial of some of them and the definition of others, benefiting from the books of the sciences of the Qur’an and interpretation. What the researcher has reached is that context plays a key role in all of this, with many other goals such as exaggeration and an indication of the specialization of some names in the Divine Essence, and other causes and goals mentioned in the folds of this research.